ANALISA PERBANDINGAN PRESSURE DROP METODE LOCKHART MARTINELLI, HOMOGENOUS DAN HARRISTON FREESTON DARI DEMISTER KE TURBIN PADA UNIT 2 PLPT LAHENDONG - Rigitha Petrisia Raco; Rolles Nixon Palilingan; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
The development of technology, population and inovation from day to day is increasing. This causes the world's energy needs to increase as well. This causes both developed and developing countries including Indonesia to take advantage of every alternative available energy resource, both renewable energy and non-renewable energy. One of the uses of renewable energy for national energy sufficiency is geothermal resources, Indonesia's strategic location causes Indonesia to have a lot of potential geothermal resources and because of that these geothermal resources must be processed as efficiently as possible to help meet national energy needs. One of the causes of the reduction in the efficiency of processing geothermal resources is the pressure drop that occurs from the demister to the turbine, this study aims to determine the pressure drop that occurs from the demister to the turbine at PLTP-2 Lahendong using 3 methods, namely Lockhart Martinelli, Homogenous and Harrison Freeston. . The results of the calculation of these 3 methods are then compared with real data in the field to find out which method is the most aaccurate and closest to use. Based on research, the turbine inlet pressure from the Homogenous method, Lockhart Martinelli and Harisson Freeston are 6.59bar, 7.25bar and 7.84 bar respectively and the level of accuracy compared to real data is 92%, 97% and 90%, respectively.